20.1k views
0 votes
The indicated function y1(x) is a solution of the given differential equation. Use reduction of order or formula (5), as instructed, to ?nd a second solution y2(x).

y``+2y`+y=0

User Mbesson
by
4.5k points

1 Answer

5 votes

Answer:

Explanation:

We will use the reduction of order to solve this equation. At first, we need a solution of the homogeneus solution.

Consider the equation
y''+2y'+y=0 We will assume that the solution is of the form
y=Ae^(rx). If we plug this in the equation, we get


Ae^(rx)(r^2+2r+1)=0

Since the exponential function is a positive function, and A should be different to zero to have non trivial solutions, we get


r^2+2r+1=0

By using the quadratic formula, we get the solutions


r= \frac{-2\pm \sqrt[]{4-4}}{2}=-1

So one solution of the homogeneus equation is of the form
y=Ae^(-x). To use the reduction of order assume that


y = v(x)y_h

where
y_h = Ae^(-x). We calculate the derivatives and plug it in the equation


y' = v'y_h+y_h'v


y'' = v''y_h+v'y_h'+y_h'v'+y_h''v = v''y_h+2v'y_h+y_h''v


(v''y_h+2v'y_h'+y_h''v)+2(v'y_h+y_h'v)+vy_h = 0

If we rearrange the equation we get


v''y_h+(2y_h'+2y_h)v'+v(y_h''+2y_h'+y_h)=0

Since
y_h is a solution of the homogeneus equation we get


v''y_h+(2y_h'+2y_h)v'=0

If we take w = v', then w' = v''. So, in this case the equation becomes


w'y_h+(2y_h'+2y_h)w=0

Note that
y_h' = -1y_h so


w'y_h=0. Since
y_h cannot be zero, this implies

w' =0. Then, w = K (a constant). Then v' = K. So v=Kx+D where D is a constant.

So, we get that the general solution is


y = vAe^(-x) = (Kx+D)Ae^(-x) = Cxe^(-x) + Fe^(-x) where C, F are constants.

User Enesn
by
4.4k points